UJI ANTAGONIS Trichoderma sp. TERHADAP FUNGI PATOGEN Pestalotiopsis sp. PENYEBAB PENYAKIT HAWAR DAUN PADA TANAMAN Eucalyptus - Khaerani, Nuraliefah; Haryani, Tri Saptari; Lelana, Neo Endra (Ekologia: Jurnal Ilmiah Ilmu Dasar dan Lingkungan Hidup, 2024)
Leaf blight disease has become one of the significant ailments in Eucalyptus spp. forest plants. This disease can lead to plant growth disruption and even plant mortality. This research aims to evaluate the antagonistic abilities of several Trichoderma isolates against Pestalotiopsis fungi associated with Eucalyptus leaf blight disease. The research was conducted using the dual culture method, wherein both Trichoderma isolates and the pathogen were cultivated on the same petri dish. The obtained data were analyzed using ANOVA at a 5% significance level, followed by the Duncan test in case of significant differences. The results of BLAST analysis of pathogens causing leaf blight have the highest similarity with Pestalotiopsis uvicola, which is equal to 99.82%. The Results test antagonist show percentage inhibition Trichoderma to pathogen Pestalotiopsis biggest showed by isolate TL122 ie of 65.333%, followed with isolates TL411 and TL631 ie consecutive by 54.49% and 49.33%. The T.L.122 isolate was declared to be the most effective as a potential antagonist fungus against the Pestalotiopsis pathogen which causes leaf blight in Eucalyptus plants.